Current Challenges of Plastic Surgical Care in Sub-Saharan Africa (Maputo, Mozambique). Issue 8 (August 2018) - Guzman, Kevin J.; Gemo, Natacha; Martins, Deborah B.; Santos, Pedro; DeUgarte, Daniel A.; Ademo, Fatima; Kulber, David; Issufo, Celma
Abstract : Background: Limited data exist on plastic surgery practices in Sub-Saharan Africa. The aim of this study was to characterize the spectrum of disease and operative procedures at a teaching hospital in Maputo, Mozambique to help understand the challenges of providing care for the local providers and to provide contextual relevance for training through partnerships. Methods: A mixed-methods approach was utilized to perform an ongoing needs assessment. A retrospective review was performed of plastic surgery operative records, ward admissions records, and death records in a tertiary-care hospital in Maputo, Mozambique for the period January 2015 to December 2015. Results: Limited resources (equipment, block-time, personnel, and perioperative services) were observed. The most common diagnoses for the 455 patients evaluated were burns (44%) and neoplasms (17%). Congenital abnormalities accounted for only 1% of the patient diagnoses. Of the 408 procedures performed, the majority were skin grafts (43%) and skin excisions (31%). Sepsis from burns accounted for 70% of documented deaths (14/20). The mean number of days to skin grafting for inpatients was 53 days. Conclusion: We observed a large burden of burns and skin graft procedures at a public referral teaching hospital in Mozambique. Our findings provide contextual relevance to help focus public health efforts and improve plastic surgery training and practices.